Patagonian toothfish (Dissostichus eleginoides) stocks in South American waters and its implications for fishery management - Otto C. Wöhler; Patricia A. Martínez; Gonzalo H. Troccoli; Emiliano J. Di Marco (Marine and Fishery Sciences)
Patagonian toothfish (Dissostichus eleginoides) is a highly prized resource in markets due to the quality of its meat. The Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) implemented controls and regulations in response to the sharp rise in the illegal fishing of D. eleginoides in the 1990s. Today, four fisheries in waters close to the southern tip of South America are managed in accordance with stringent sustainability standards. Even though they are separate management units, both abundance assessments and annual catch allocations are conducted using different criteria regarding stock considerations across the region, leaving one of the fundamental premises of fisheries management unclear. This study examines historical data and recent research to explore the potential differentiation between Patagonian toothfish populations in South American waters, which is crucial for the management of diverse fisheries. Genetic studies, otolith microchemistry, morphometry, parasitic fauna, tagging programs, reproductive characteristics, and the impact of ocean circulation on dispersal and recruitment were analyzed. Tagging studies in the southern hemisphere oceans confirm the species’ affinity to specific habitats, suggesting minimal fish exchange between South American fishing grounds. From a fisheries perspective, this review suggests the existence of distinct stocks of the species structured along the shelf and slope of the southern cone of America based on reproduction areas along the continental shelves and slope, the diverse parasitic fauna, the variability in stable isotopes and trace elements of otoliths, and the little significant exchange of fish between current fishing grounds. All of this could lead to considering the D. eleginoides fishery as independent exploitation units.